2013
DOI: 10.1007/s10346-012-0377-x
|View full text |Cite
|
Sign up to set email alerts
|

A slope failure caused by drainage cutoff through the advancement of seasonal frost, Hudson Bay Lowland

Abstract: A slope failure caused by drainage cutoff through the advancement of seasonal frost, Hudson Bay Lowland Abstract A failure occurred between December 14 and 17, 2008 in the upper part of a 45-m high, northwest facing bank of the Nelson River in northern Manitoba (56.687°N, 93.777°W). The slope failure occurred at a spring site in a bay associated with a buried valley. The sediment input to the river from this event is roughly 20,000 to 25,000 m 3 . The source zone is made up of 25 m of water-bearing sand and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Extensive studies have shown that slope failure in permafrost areas is associated with the thawing of the active layer 1,2 , and the decay of strength at the freeze-thaw interface is the key to causing slope instability 3 . Moisture content and temperature are the two most important factors affecting the strength of frozen soil [4][5][6] . Meanwhile, a large number of studies have confirmed that the change of strength is mainly realized by changing the state of water through temperature [7][8][9] .…”
Section: Experimental Study On Shear Characteristics Of the Silty Cla...mentioning
confidence: 99%
“…Extensive studies have shown that slope failure in permafrost areas is associated with the thawing of the active layer 1,2 , and the decay of strength at the freeze-thaw interface is the key to causing slope instability 3 . Moisture content and temperature are the two most important factors affecting the strength of frozen soil [4][5][6] . Meanwhile, a large number of studies have confirmed that the change of strength is mainly realized by changing the state of water through temperature [7][8][9] .…”
Section: Experimental Study On Shear Characteristics Of the Silty Cla...mentioning
confidence: 99%
“…Studies have shown that the instability of slopes in cold regions is mostly related to the thawing of frozen soil [8,9]. Water content and temperature have a pivotal role in the strength variation of frozen soil [10,11]. Qin et al [12] and Zhou et al [13] found that a slight increase in temperature could cause a reduction of strength when the temperature is close to the freezing point of ice in frozen soi.…”
Section: Introductionmentioning
confidence: 99%
“…Ice bonds in frozen soil combine solid particles together, change the interaction between soil components and have a great impact on the mechanical behavior of soil. Internal temperature, humidity, and stress of frozen soil affect one another [25][26][27]. De Guzman et al [28] found that in a certain temperature range, the strength of shear failure surface is positively proportional to negative temperature.…”
Section: Introductionmentioning
confidence: 99%